Job-Related Variables and Age Differences on Turnover Intention in Malaysian SMEs - Thien, Leon Hung Wui (2017)
This study aims to determine the main job-related factors that predict turnover intention among employees in Malaysian small and medium sized enterprises (SMEs). This study also looks into age differences in overall turnover intention and the independent variables between younger and older employee groups. Primary data was collected from 120 participants who are employed in a Malaysian SMEs in the form of questionnaires. Correlation and multiple regression analyses were performed on two control variables and four independent variables. The independent variables in this study are job autonomy, social support, job stress and leadership. The results of the analyses revealed that only job autonomy, job stress and leadership were found to strongly predict turnover intention. Overall turnover intention in younger employees under age 40 was higher than the older employees. The findings from the age split analyses showed that all four independent variables were unable to significantly predict turnover intention among the older employees but this finding could largely be due to several limitations of the research. The conclusion drawn from these findings was that SMEs should have the owner-managers be more engaged and supportive towards their employees. SMEs should also implement policies to reduce work-related stress and allow the employees to have a higher degree of autonomy over their work. Finally, SMEs should be more observant of the changes in behaviour and attitudes of younger employees to be able to detect early stages of development of turnover intention.